A Multimodal Analysis of Tourism Brochures for Advertising Tourist Attraction in Mandeh Island, West Sumatra - Sintia Furnama; Rusdi Noor Rosa (English Language and Literature, 2020)
This study aims at describing verbal and visual elements in Sumbar Holiday tourism brochure of Mandeh Island, West Sumatera. The verbal and visual elements are analyzed by using Cheong′s (2004) generic structure. The researcher used descriptive research method. The data in this research were verbal and non-verbal texts found in Sumbar Holiday tourism brochure of Mandeh Island. The brochure was downloaded from travel and tour agent Instagram account that is chosen randomly. The result of the study reveals that the brochure have all generic structure which is lead, display, emblem (verbal), announcement, enhancer, emblem (visual), tag, and call-and-visit information. The finding of Sumbar Holiday brochure fully supports Cheong′s (2004) theory. The verbal and visual elements support each other and cohere to convey a message to the reader. The message conveyed to readers become more persuasive, and it arouses their interest to use the tour and travel company service.